Nematostatic activity of isoprenylated guanidine alkaloids from Pterogyne nitens and their interaction with acetylcholinesterase - Coqueiro, Aline [UNESP]; Fernandes, Daniara Cristina [UNESP]; Danuello, Amanda [UNESP]; Regasini, Luis Octávio [UNESP]; Cardoso-Lopes, Elaine Monteiro; Young, Maria Cláudia Marx; Brandão Torres, Luce Maria; Campos, Vicente Paulo; Silva, Dulce Helena Siqueira [UNESP]; da Silva Bolzani, Vanderlan [UNESP]; de Oliveira, Denilson Ferreira (Elsevier, 2023)
Although new nematicides have appeared, the demand for new products less toxic and more efficient for the control of plant-parasitic nematodes are still high. Consequently, studies on natural secondary metabolites from plants, to develop new nematicides, have increased. In this work, nineteen extracts from eleven Brazilian plant species were screened for activity against Meloidogyne incognita. Among them, the extracts of Piterogyne nitens showed a potent nematostatic activity. The alkaloid fraction obtained from the ethanol extract of leaves of P. nitens was more active than the coming extract. Due to the promising activity from the alkaloid fraction, three isoprenylated guanidine alkaloids isolated from this fraction, galegine (1), pterogynidine (2), and pterogynine (3) were tested, showing similar activity to the alkaloid fraction, which was comparable to that of the positive control Temik at 250 μg/mL. At lower concentrations (125−50 μg/mL), compound 2 showed to be the most active one. As several nematicides act through inhibition of acetylcholinesterase (AChE), the guanidine alkaloids were also employed in two in vitro AChE assays. In both cases, compound 2 was more active than compounds 1 and 3. Its activity was considered moderated compared to the control (physostigmine). Compound 2 was selected for an in silico study with the electric eel (Electrophorus electricus) AChE, showing to bind mostly to the same site of physostigmine in the AChEs, pointing out that this could be the mechanism of action for this compound. These results suggested that the guanidine alkaloids 1, 2 and 3 from P. nitens are promising for the development of new products to control M. incognita, especially guanidine 2, and encourage new investigations to confirm the mechanism of action, as well as to determine the structure-activity relationship of the guanidine alkaloids.
Keywords: Biodiversity; Galegine; Meloidogyne incognita; Nematodes; Pterogynidine; Pterogynine